Pattern of internet usage at the rural library among rural youth in Malaysia - Omar, Siti Zobidah; Mazuki, Raidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Mediterranean Center of Social and Educational Research, 2016)
The main aim of this study is to identify the pattern of Internet usage at the rural library among rural youths in Malaysia (aged between 15 to 40 years old). As a developing country, the internet usage among rural youths is a crucial issue in terms of the digital divide between rural and urban youths. The study was quantitative in nature, and via a multi-stage simple-random sampling, a total of 400 rural library users from four selected districts had been selected as the respondents. The SPSS software was used to run a proper analysis. The results showed that the mean score recorded for internet usage among the rural youths was 91.12 minutes and the majority of them were aged below 20 years old. Remarkably, the local development is seen as the motivation for the rural youths, yet it is probably the least manageable. Recommendations for future research and implications for practice are presented in the conclusion.